REALITAS PENDIDIKAN NILAI DI LINGKUNGAN KELUARGA, SEKOLAH DAN MASYARAKAT - Sulton Sulton (Postgraduate Program Magister Pendidikan Agama Islam, 2016)
Demoralization and dehumanization phenomenon that is happening has urged the crisis of values and morals in this country. Tactics of corruption, collusion, nepotism, murder, fights, abuse, fraud, bribery, fraud, mafia law, the realtor case and the crisis of moral values and the other is one of the markers. Not only external factors, but also internal factors named education of moral and values whether in the family, school or society is believed to be the main cause. Nowadays, the existence of educational value in these three sectors is being hit by the crisis and urged to be studied and restored its roles. The family must not only become a symbol of attachment members, but also it must take the first and main role of parents as primary members to do the transformation and moral values to their children. Meanwhile, the school is more than just the pursuit of academic achievement targets and it is also required to design its overall program that integrated with the education of moral values needed by the children. The society, certainly expected to be a great home for the growth and development of value system as the support and orientation of values and morals by its members including the children. For these reasons, through government regulation and policy are expected to take a role in guiding and heading the process of transformation and moral values in the three education sectors. Furthermore, the elite and stakeholders of educational value such as parents, teachers, and leaders are expected to provide good examples and role models, as one of practical form in providing comprehension, guidance, and awareness within the framework of exsited morals and values.